Efficacy of nucleos(t)ide analogues(NAs) in preventing virus reactivation in oncology patients with HBV infection after chemotherapy or surgery: A network meta-analysis - Zhao, Yuqing; Song, Yingying; Zhang, Huan; Qu, Tongshuo; Axinbai, Malina; Yang, Yidian; Zhang, Liping (Frontiers in Oncology, 2023)
Objective: In this study, we aimed to perform a network meta-analysis to compare the effectiveness of NAs in decreasing the reactivation of HBV, reducing chemotherapy disruption, and improving survival in oncology patients. Methods: Relevant randomized controlled trials (RCT) evaluating the impact of NAs in HBV infected-related oncology patients were retrieved from electronic databases. The outcome indicators included reactivation rate, survival rate of 1 to 3 years after treatment, and chemotherapy disruption rate. The studies were evaluated for bias using the RCT risk of bias assessment tool recommended in the Cochrane Handbook. The risk ratio (RR) was used to compare the outcome indicators for the anti-viral treatment, and the surface under the cumulative ranking curves (SUCRA) was used to identify the optimal therapeutic regime. Results: A total of 67 trials containing 5722 patients were included in this study. Regarding the reduction of reactivation rate, entecavir, lamivudine, adefovir alone were less effective than the combination of lamivudine and entecavir (94.9%), with RR values ranging from 3.16 to 3.73. However, based on SUCRA, the efficacy of telbivudine (80.3%) and the combination of lamivudine and adefovir dipivoxil (58.8%) were also acceptable. Entecavir (RR values ranging from 1.25 to 1.50) and lamivudine (RR values ranging from 1.27 to 1.35) can prolong the survival rate of patients at 1-3 years, and were better than adefovir dipivoxil in the comparison of 1-year survival rate. The RR values were 1.18 and 1.19, respectively. And entecavir 's ranking in SUCRA was more stable. Entecavir, lamivudine, and tenofovir all reduced chemotherapy interruption rates compared with no antiviral therapy, especially for tenofovir. Conclusions: Current evidence shows that lamivudine combined with entecavir, telbivudine, and lamivudine combined with adefovir dipivoxil were the most effective in preventing virus reactivation in HBV infected-related cancer patients treated with chemotherapy. Entecavir had the most stable effect on survival, while tenofovir had the best impact on reducing the chemotherapy disruption rate. Due to limited quality and quantity of the included studies, more high-quality studies are required to verify the above conclusions.